Review of mechanical properties of short fibre reinforced geopolymer composites - Ahmed, Shaikh (Elsevier BV, 2013)
Concrete exhibits brittle behaviour due to its low tensile strength. The addition of fibres, either short or continuous, changes its brittle behaviour to ductile or quasi-ductile with significant improvement in tensile strength, tensile strain, toughness and energy absorption capacities. The binder in the fibre reinforced cement composites (FRCCs) is mainly Portland cement. The recent environmental awareness in construction industry promotes the use of alternative binders to partially or fully replace the cement as its production creates environmental pollution due to release of CO2 into atmosphere. Recent years have seen a great development in new types of inorganic cementitious binders called “geopolymeric cement” around the world. This prompted its use in concrete, which improves the greenness of ordinary concrete. Efforts have been made to replace the cement based binder in the current FRCC with “geopolymeric” binder resulting in fibre reinforced geopolymer composites (FRGCs), which is greener than the former one. The development of FRGC is relatively new in the field of construction materials. This paper presents the state-of-the-art development of short fibre reinforced FRGC and its mechanical properties with emphasis on compressive strength, tensile strength, flexural strength, impact strength and toughness capacities. The durability properties of FRGC are also discussed in this paper. The recent development on ductile fibre reinforced geopolymer composites (DFRGCs) exhibiting deflection hardening and multiple cracking behaviour in flexure is also presented here.